Chapter Coastal archaeological evidence in the Bay of Naples: vulnerability and issues for conservation and enhancement - Aveta, Claudia (Firenze University Press, 2025)
There is no region in Italy and, perhaps, in the world that presents such a wealth of archaeological evidence, even underwater, as Campania and, in particular, along the coasts of the Bay of Naples: a site that includes all the territories bordering the gulfs of Naples and Pozzuoli, including the islands of Procida, Ischia and Capri. It is precisely the extraordinariness of this richness that makes it a particularly complex case, bearing in mind that we are dealing with highly urbanised areas and, therefore, decidedly exposed to human action. This contribution attempts to outline the complex problems of the coastal archaeological areas, including underwater areas, in the Bay of Naples, starting from the definition of their consistency and varied typology and the phenomena of degradation that characterise them, to arrive at a definition of the risks to which they are exposed and to point out possible directions consistent with desirable urban regeneration processes: among these are the significant experiences of the submerged archaeological parks of Baia and Gaiola